A New Approach to the Star Data of Early Planispheric Astrolabes - Strano, Giorgio (Medieval encounters, 2017)
During the twentieth century, scholars attempted to date early astronomical instruments by the scientific information discernable in their design. In particular, they devised “methods” to date planispheric astrolabes by the position of the vernal equinox on the calendar scale or by the precessional effect over the star coordinates. Such methods usually overlooked the many problems behind the instruments’ design and construction and the vicissitudes in a particular object’s history. Criticisms of the naiveté of the scientific approach did not persuade scholars with an astronomical background. They remained convinced of the supreme explanatory power that the present knowledge has for deciphering the past. The criticisms, instead, dissuaded scholars with a historical background from paying attention to the scientific data. They felt comfortable in analysing scientific relics on the basis of other types of evidence, such as textual sources, iconography, and style. The star coordinates of early planispheric astrolabes, as witnessed in their star pointers, can neither be regarded nor treated as the data of present science. Even if they do not describe the sky at the very moment of the making of the instruments, they may, nevertheless, be considered as non-textual sources that contain precious information. The star coordinates on the astrolabe retes may in fact connect groups of instruments with early star tables.